Kahoot-Based PAI Learning Evaluation - Rezani Ahzim; Sepriboy Saputa; Deri Wanto; Mirzon Daheri (CV Media Inti Teknologi, 2023)
Evaluation in learning is an action or process to determine the value of learning success of a student after the learning process. The purpose of this research is to find out the Kahoot Application-based PAI Learning Evaluation at SDN 32 Rejang Lebong. The rapid development of technology in the field of education requires educators to be able to innovate in utilizing media, one of which is the kahoot application. Research using qualitative research with a type of case study research. The research methods used in this research are interviews, documentation and observation. For data analysis, researchers apply the triangulation method by rechecking. In this study, the results obtained from the use of the kahoot application as an alternative in evaluating PAI learning at SDN 32 Rejang Lebong have maximized its use. Through this kahoot application, it attracts students' interest in answering questions and this kahoot application can also see the extent of students' understanding of the material that has been given by educators with the aim that an educator can evaluate learning and can map difficult questions for students to be reinforced or review difficult material with different ways of teaching.